IMPLEMENTASI MANAJEMEN STRATEGIK DALAM MANAJEMEN HUMAS DI LPI - Muhammad Afriansyah Novianto; Maulidia Maulidia (Tarbawi, 2022)
Public relations, or PR, is the art of creating better understanding among the public so that it can increase public trust in certain individuals or institutions. In the context of educational institutions, public relations are a part of management related to interactions between educational institutions and the community. The purpose of the discussion is to find out the implementation of strategic management in educational institutions and public relations management in Islamic educational institutions. This discussion uses literature using the literature study method. data collection techniques, namely documentation such as books, journals, magazines, and others. Results of the discussion: 1) In implementing school public relations strategies, there needs to be an appropriate strategy to achieve educational goals, especially in increasing parent participation. One way to increase the participation of parents of students is to build a good relationship between the school and parents. 2) Humanitarian management in educational institutions itself is defined as a process of planning, organizing, directing, coordinating, mobilizing, communicating, and evaluating that involves all stakeholders in the school environment to achieve educational goals effectively and efficiently. The essence of implementing public relations management in Islamic boarding schools is almost the same as that of other Islamic public relations institutions, namely designing public relations activities based on the values of Al-Qur’an and Al-Hadith.